A multiple case study on maternity outpatients' perceptions of comfort in relation in the interior design of waiting areas of selected two public lying-in clinics in Quezon City - Tolentino, Rochelle M.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT This multiple case study sought to determine the perceptions of comfort among maternity outpatients in relation to the interior design of the waiting areas of two selected lying-in clinics in Quezon City, namely, Batasan Hills Lying-in Clinic and Betty Go-Belmonte Lying-in Clinic. Data was gathered through observations, photo documentation, survey and interviews. Purposive sampling was used to select ten maternity outpatients from each of the two lying-in clinics as participants of the survey, while convenience sampling was used to select five maternity outpatients from each of the said clinics for the interviews in order to determine their perceptions as well as level of comfort in relation to the interior design of the waiting area in the lying-in clinic that they frequent for their medical needs. Through observations and photo documentation, each of the two waiting areas was evaluated according to five (5) elements of interior design pertaining to the waiting area's color scheme, furniture design, furniture layout, lighting and interior finishes. Rybczynski's Onion Theory of Comfort (1986) was utilized as the study's theoretical framework and basis for analyzing the results. Findings from both the survey and interviews revealed that the respondents' perceptions of comfort in relation to the interior design of the lying-in clinic's waiting area were generally positive as evidenced by the following attributes that the respondents associated with the condition of the interior space: pleasure, efficiency, domesticity, functionality, support, convenience and ease. This study recommends that future similar researches on the interior design of health facilities and other related institutions be conducted addressing the needs of various types of users.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Women's hospitals -- Philippines -- Quezon City -- Case studies